2022
DOI: 10.1186/s12933-022-01728-w
|View full text |Cite
|
Sign up to set email alerts
|

Stress hyperglycemia ratio and in-hospital prognosis in non-surgical patients with heart failure and type 2 diabetes

Abstract: Objective To evaluate the impact of stress hyperglycemia on the in-hospital prognosis in non-surgical patients with heart failure and type 2 diabetes. Research design and methods We identified non-surgical hospitalized patients with heart failure and type 2 diabetes from a large electronic medical record-based database of diabetes in China (WECODe) from 2011 to 2019. We estimated stress hyperglycemia using the stress hyperglycemia ratio (SHR) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
(57 reference statements)
2
17
0
Order By: Relevance
“…Notably, the U-shaped or J-shaped association was not significant in the subgroup of patients without diabetes, consistent with our findings [ 8 ]. Moreover, Zhou et al found a U-shaped association between SHR and in-hospital cardiac, kidney, and infectious adverse events in non-surgical hospitalized patients with type 2 diabetes and heart failure [ 32 ]. In addition, one study consisting of 3750 AMI patients admitted to 35 hospitals in Japan found that severe hyperglycemia (glucose ≥ 11 mmol/L) and euglycemia (glucose < 7 mmol/L) was associated with higher mortality compared to moderate hyperglycemia (glucose 9 to 11 mmol/L) in patients with a history of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the U-shaped or J-shaped association was not significant in the subgroup of patients without diabetes, consistent with our findings [ 8 ]. Moreover, Zhou et al found a U-shaped association between SHR and in-hospital cardiac, kidney, and infectious adverse events in non-surgical hospitalized patients with type 2 diabetes and heart failure [ 32 ]. In addition, one study consisting of 3750 AMI patients admitted to 35 hospitals in Japan found that severe hyperglycemia (glucose ≥ 11 mmol/L) and euglycemia (glucose < 7 mmol/L) was associated with higher mortality compared to moderate hyperglycemia (glucose 9 to 11 mmol/L) in patients with a history of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…While stress hyperglycemia may not potentially distinguish among diverse causes of absolute hyperglycemia, SHR is a combined measure of a patient’s acute-phase and chronic glycemia values, it reflects the true stress hyperglycemia state and has been found to be a potential determinant of adverse risk in multiple cardiovascular diseases [ 32 ]. Zhou et al found that both high and low SHR indicate a poor prognosis in patients with HF and type 2 diabetes during hospitalization [ 22 ]. In a recent study, a U-shaped association was identified between the SHR and all-cause, cardiac death, and HF readmission in individuals with acute decompensated HF and diabetes after a 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have assessed its role across various cardiovascular diseases, indicating its potential as a predictor of future risk, regardless of diabetes presence [ 18 21 ]. While recent studies have explored the impact of SHR on short- and long-term outcomes in diabetic HF patients, there is no data on its specific impact on the long-term prognosis of HFpEF, encompassing both diabetic and non-diabetic individuals [ 22 , 23 ]. Consequently, there is a need to clarify the potential role of SHR within clinical risk strategies for patients with HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies indicate that SHR is independently associated with short-term and long-term adverse outcomes in acute coronary syndrome (ACS) and short-term adverse outcomes in acute myocardial infarction (AMI) [ 8 13 ]. A study involving 2875 Chinese adults with type 2 diabetes and heart failure found that both higher and lower SHR patients had poor prognoses [ 14 ]. Regarding the correlation between SHR and cerebrovascular diseases, a two-center prospective study showed that after adjusting for covariates, for each 1-unit increase in SHR, the risk of early hematoma expansion in spontaneous intracerebral hemorrhage (ICH) patients increased by 16.535 times (95% CI: 3.572–76.543, p < 0.001), indicating an independent correlation between SHR and early hematoma expansion in ICH patients.…”
Section: Introductionmentioning
confidence: 99%